2020
DOI: 10.1038/s41598-020-68691-y
|View full text |Cite
|
Sign up to set email alerts
|

Degradome, small RNAs and transcriptome sequencing of a high-nicotine cultivated tobacco uncovers miRNA’s function in nicotine biosynthesis

Abstract: tobacco (Nicotiana tabacum) is considered as the model plant for alkaloid research, of which nicotine accounts for 90%. Many nicotine biosynthetic genes have been identified and were known to be regulated by jasmonate-responsive transcription factors. As an important regulator in plant physiological processes, whether small RNAs are involved in nicotine biosynthesis is largely unknown. Here, we combine transcriptome, small RnAs and degradome analysis of two native tobacco germplasms YJ1 and ZY100 to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 66 publications
(100 reference statements)
0
3
1
Order By: Relevance
“…On this basis, a total of 5 known miRNAs and 320 novel miRNAs were identified in "High Noon" and "Roufurong" floral tissues. Differing from a large number of known miRNAs in other species such as P. lactiflora (Zhao et al, 2017a), L. chinensis (Liu et al, 2017), and N. tabacum (Jin et al, 2020), the number of novel miRNAs identified in our study was much higher than that of known miRNAs. It may be attributed to the specificity of tree peony genome.…”
Section: Discussioncontrasting
confidence: 84%
“…On this basis, a total of 5 known miRNAs and 320 novel miRNAs were identified in "High Noon" and "Roufurong" floral tissues. Differing from a large number of known miRNAs in other species such as P. lactiflora (Zhao et al, 2017a), L. chinensis (Liu et al, 2017), and N. tabacum (Jin et al, 2020), the number of novel miRNAs identified in our study was much higher than that of known miRNAs. It may be attributed to the specificity of tree peony genome.…”
Section: Discussioncontrasting
confidence: 84%
“…After long-term business development and demonstration, relational database has been widely used. Since then, the storage and utilization of data have entered a new era [13]. Dean published "Capital Budget," which changed the focus of financial management from the emphasis on external financing to the rational allocation of funds within the company, which made a qualitative leap in the company's financial management [14].…”
Section: Related Workmentioning
confidence: 99%
“…In tobacco, comprehensive screenings of non-coding RNA species have revealed the relevance of some of these RNAs in regulating genes in the nicotine pathway ( Chen et al , 2019 ; Jin et al , 2020 ; Zheng et al , 2022 ). One pair of regulatory RNAs, the miRNA nta-miRX27 and its corresponding eTM nta-TMX27, target a key nicotine biosynthesis gene, QPT2 , to regulate nicotine levels in tobacco ( Li et al , 2015 ).…”
Section: Regulationmentioning
confidence: 99%